The York Vintners’ ‘The Marriage at Cana’ and the Puzzle of Pageants Withheld from the Register - Groeneveld, Leanne (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2023)
Opening with the character of Architriclinus, the York Vintners’ pageant ‘The Marriage at Cana’ likely bolstered their claims over the right to search and sell sweet and other wines in conflicts with the Spicers and Mercers. The Vintners’ failure to submit their pageant for transcription into the York Register possibly signals resentments felt and privileges enjoyed by these specialist merchants – resentments and privileges perhaps shared by the only other guild to withhold their original from the city clerk despite repeated calls for its submission: the Ironmongers.